1998
DOI: 10.1093/tropej/44.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Exclusive breastfeeding among women on the plantations in Sri Lanka

Abstract: A cross-sectional questionnaire survey, using the current status method for the assessment of breastfeeding, was conducted among women working in the plantations in Sri Lanka. The exclusive breastfeeding rate was 32.4 per cent. The mothers' return to work and the feeling of having insufficient milk were significantly and negatively associated with exclusive breastfeeding. Women will sometimes start with powdered milk several weeks before going back to work, suggesting that work itself is not the only reason fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The urban sector in this study was a socioeconomically diverse and densely populated region, with a considerable number of families belonging to both the highest and the lowest socio-economic groups and a high proportion of working mothers.The tea estate sector is a relatively homogeneous community with a socio-economically poor, less educated tea estate worker population and children are kept in child-care centres when their mothers are at work in the tea estates. Comparatively low breastfeeding practices in the tea estate sector had been reported in a previous study of plantation sector and in the analysis of Sri Lanka DHS in 2000 (Sorensen et al 1998;Senarath et al 2010b). Also, many differences were seen across provinces indicating the inequalities across different regions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The urban sector in this study was a socioeconomically diverse and densely populated region, with a considerable number of families belonging to both the highest and the lowest socio-economic groups and a high proportion of working mothers.The tea estate sector is a relatively homogeneous community with a socio-economically poor, less educated tea estate worker population and children are kept in child-care centres when their mothers are at work in the tea estates. Comparatively low breastfeeding practices in the tea estate sector had been reported in a previous study of plantation sector and in the analysis of Sri Lanka DHS in 2000 (Sorensen et al 1998;Senarath et al 2010b). Also, many differences were seen across provinces indicating the inequalities across different regions.…”
Section: Discussionmentioning
confidence: 67%
“…The tea estate sector is a relatively homogeneous community with a socio‐economically poor, less educated tea estate worker population and children are kept in child‐care centres when their mothers are at work in the tea estates. Comparatively low breastfeeding practices in the tea estate sector had been reported in a previous study of plantation sector and in the analysis of Sri Lanka DHS in 2000 (Sorensen et al . 1998;Senarath et al .…”
Section: Discussionmentioning
confidence: 68%
“…It is possible that in selected population groups, other factors could influence suci changes in EBFpractice. For example, Sorenson et al (8) in their study in theplantation sector in Sri Lanka reported an EBF rate of 73% during the first month, which showed a marked decline to 23% during the second month. Thelikely explanation for this difference is that the women in the plantations are a predominantly working population and the change in the EBF practices was related to the mother having to 'return to work', A study carried out in 12 out of the 24 districts in Sri Lanka in theearly '80s, identified employment of women outside the home as a factor that influenced early introduction of artificial milk (4).…”
Section: Resultsmentioning
confidence: 99%
“…Mothers who were not visited by a Public Health Midwife at home during pregnancy were also at a higher risk for not initiating timely breastfeeding (adjusted OR = 1.81; 95% CI, 1. 13 Infants whose mothers had ever been employed had a higher risk of being bottle-fed (adjusted OR = 1.86; 95% CI, 1.13 to 3.05; p < .05), as did infants of mothers who had been formerly married (adjusted OR = 8.96; 95% CI, 1.86 to 43.18; p < .01) (table 5). Mothers who had completed secondary education had lower bottle-feeding rates than mothers without any schooling (adjusted OR = 0.27; 95% CI, 0.08 to 0.92; p < .05).…”
Section: Determinants Of Feeding Indicatorsmentioning
confidence: 99%